Transition Pathway Toward Agroecology in Agroforestry Systems: Case of Kesra - Shiri, Zahra; Alary, Veronique; Ouerghemmi, Hassen; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Majri, Rihab; Rudiger, Udo; Frija, Aymen; Idoudi, Zied; Souissi, Asma; Dhehibi, Boubaker; Mannai, Amal; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
The mountain of Kesra is located at an altitude of 1245 m with a very uneven relief. It belongs to the upper semi-arid bioclimatic stage. The range of soils is very diverse due to the extreme variability of substrates, climates, and plant species. Despite the richness of natural resources and heritage, and the ancestral know-how of local populations, the region of Kesra, continues to suffer from economic and social underdevelopment. Standard applications, which do not take into account the specificities of each area, often do not achieve the objectives of ecodevelopment and sustainability. The application of a holistic agroecological transition approach in this rural mountain area requires an inclusive co-design which takes into consideration the socio-ecological context (Natural resources use, agricultural practices, agroforestry, etc.). So, the main objective was to define and build context-specific agroecological transition pathways throw a solid methodology which combines literature review, consultation, and focus group discussions. The visioning approach was conducted with 12 farmers from the community to reflect on the state of agriculture in Kesra and to identify a desirable future of agriculture in 10 years (2022-2032) from their own perspective. This vision was discussed and debated referred to the 13 principals of agroecology. The AE transition pathway identified in Kesra suggests an emphasis on the diversification of local and natural based products to insure synergies between system components as a basis of a swift transition. The resulting impact pathway promotes increasing resilience to market and climate change, economic autonomy, diversifying market, and promotion of local products. Based on this approach and other research activities a set of actions will be executed during 2023 and 2024 to monitor the co-designed transition pathways and to scaling-up the agroecological transition in the mountainous areas like Kesra.